Accessing abortion outside jurisdiction following legalisation of abortion in the Republic of Ireland. Issue 3 (23rd December 2020) - Bras, Sierou; Gomperts, Rebecca; Kelly, Michaela; Aiken, Abigail R A; Conlon, Catherine
Abstract : Background: After having one of the most restrictive abortion laws worldwide, Ireland legalised abortion in January 2019. We examine how legalisation impacted on demand for online telemedicine outside the jurisdiction. Methods: We analysed anonymised data from 534 people from Ireland seeking online telemedicine abortion prior to legalisation (January–March and October–December 2018) and in the first 3 months following legalisation (January–March 2019). Numbers, characteristics and reasons for seeking the service before and after legalisation were compared. Content analysis of emails from people seeking the service following legalisation explored reasons for seeking care. Results: Half as many people contacted Women on Web in the 3 months immediately after legalisation as compared with contacts 12 months prior (103 vs 221). Of these, the proportion receiving the service reduced, from 72% prior to legalisation to 26% after legalisation (p≤0.001). After legalisation, access related reasons for seeking online telemedicine featured less while reasons relating to privacy, stigma and avoiding protestors featured more. Conclusions: People continued to seek abortion through online telemedicine after legalisation, though the number of contacts reduced by half and the proportion receiving the service decreased considerably. To address access issues, policy measures should promote normalisation of abortion, legislate for safe zones around providers, and consider access in situations of coercive control or abuse including the role of telemedicine in the local model of care. Abortion provided through online telemedicine continues to be an important part of providing safe, accessible abortion even after legalisation.